Analisis Fundamental Makro, Struktur Modal Terhadap Nilai Perusahaan dengan Kebijakan Manajemen, Kinerja Keuangan dan Karakteristik Perusahaan Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Mushfiroh, Luluk; Hwihanus (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to investigate the relationship between macro fundamental analysis, capital structure, and company value by considering management policies, financial performance, and characteristics of financial companies listed on the Indonesia Stock Exchange. The research method used includes analysis of historical data of financial companies listed on the Indonesia Stock Exchange within a certain time period. In this research, the variables observed include macroeconomic factors that influence the financial industry, company capital structure, company value as reflected in share prices, implemented management policies, company financial performance, and special characteristics of financial companies. The results of the analysis show that there is a signitifikancant relationship between macro fundamental analysis, capital structure and company value. Macroeconomic factors such as inflation, interest rates, and economic growth have a signitifikancant impact on a company's financial performance. Apart from that, effective management policies have also been proven to influence company value and better financial performance. This research provides valuable insights for investors, financial managers and capital market regulators to understand the factors that influence company value in the context of macro fundamental analysis and capital structure.